Analytical model for concrete cover separation of FRP strengthened RC beams with multiple steel bolts. (13th October 2020) - Zhang, Dawei; Shi, Haifeng; Zhu, Jihua; Ueda, Tamon
Abstract: In this paper, analytical models for concrete cover separation (CCS) of FRP strengthened reinforced concrete (RC) beams with multiple steel bolts were developed based on concrete tooth model for strengthened RC beams without anchors. The derivation of the models involved three major steps: (a) determination of the crack spacing (width of the concrete teeth); (b) determination of the pull‐out strength of steel bolt considering the effect of shear crack; and (c) determination of the peak load of FRP strengthened beams when CCS occurs based on the concrete tooth model. Validation test on five RC beams was conducted to investigate the effect of anchorage systems on the premature debonding of FRP strengthened RC beams. Results showed that steel bolts with enough embedding length can effectively suppress the initiation and propagation of CCS, thus improve the performance of FRP strengthened RC beams. Moreover, a database of FRP strengthened RC beams with mechanical fasteners (MFs) and failed in CCS or FRP fracture (FR) was assembled from the literature. The analytical predictions agreed well with the experimental results.